PENGARUH MODEL PEMBELAJARAN TEAMS ASSISTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR DITINJAU DARI KEMANDIRIAN - Letti Tya Intan Saputri; Hj. Hidayati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study was aimed to find out the significant difference between the students learning outcomes of natural science that were taught using a cooperative learning method Teams Assisted Individualization (TAI) design and a conventional method in terms of student independence. This study was an experimental study. The subject of this study was the seven grade students of SMPN 1 Imogiri. From seven classes, two classes randomly taken as the sample groups. Data collection techniques were done through a test and a questionnaire. All data were analyzed by using a One-Way ANACOVA test. The result revealed that the mean value of the student's score that was taught using TAI was 22,563 and those that were taught using a conventional method was 18,069. In conclusion, the hypothesis of this study was accepted. There is a significant difference between the students learning outcomes that were taught using TAI and a conventional method in terms of student independence.